Comparison of local versus spinal anesthesia in long standing open inguinal hernia repair - Goel, Anubhav; Bansal, Ankur; Singh, Akash (International Surgery Journal, 2017)
Background: Hernias are among the oldest known afflictions of human kind and elective inguinal hernia repair is commonly performed operation in general surgery. General or spinal anesthesia are still the most common types of anesthesia being used in India. Studies comparing the recovery profiles of local, general and regional anesthesia show that local anesthesia is ideal for day care surgery. Methods: This study had included 60 cases of male single sided reducible indirect long standing (more than 5 years) inguinal hernia. Patients were divided randomly into two groups of 30 each named Group A and Group B. Patients in group A were subjected to inguinal hernia mesh repair under local anesthesia and patients in group B were subjected to inguinal hernia mesh repair under spinal anesthesia. Tension free Lichtenstein hernioplasty was done in both groups. Results: Time taken in local anesthesia is higher than spinal anesthesia. Intraoperative pain is higher in local anesthesia than spinal anesthesia. There is no difference on post-operative pain. Post-operative complications are more in spinal anesthesia group. Conclusions: Patient selection is very important and patient with long history should be avoided under local anesthesia.